2021
DOI: 10.1007/s11187-021-00540-2
|View full text |Cite
|
Sign up to set email alerts
|

Digital affordances: how entrepreneurs access support in online communities during the COVID-19 pandemic

Abstract: COVID-19 has caused significant and unforeseen problems for entrepreneurs. While entrepreneurs would normally seek social support to help deal with these issues, due to social distancing, physical networks are often not available. Consequently, entrepreneurs must turn to alternative support sources, such as online communities, raising the question of how support is created in such spaces. Drawing on an affordance perspective, we investigate how entrepreneurs interact with online communities and base our qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 85 publications
(169 reference statements)
1
59
0
Order By: Relevance
“…The digital platforms will be used to advertise and sell the products [117]. The entrepreneurs can use online communities to find new collaborates, envisage new opportunities, and acquire the assistance to solve the particular problem [118]. Hence, there is no need to move the entrepreneurs from place to another for establishing their business.…”
Section: Discussionmentioning
confidence: 99%
“…The digital platforms will be used to advertise and sell the products [117]. The entrepreneurs can use online communities to find new collaborates, envisage new opportunities, and acquire the assistance to solve the particular problem [118]. Hence, there is no need to move the entrepreneurs from place to another for establishing their business.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our study demonstrates the increased significance (usefulness) of online communities as a substantial tool for providing social support [44] during disasters and pandemics such as COVID-19. Before COVID-19, discourses on the Internet's role in social capital were contentious.…”
Section: Implications Of Tam During the Covid-19mentioning
confidence: 68%
“…However, recent studies have found that online communities can be substitutional tools for providing social support, replacing traditional, offline social networks. They can be more efficient than offline networks in providing support due to their specific characteristics [44]. In particular, the benefits of virtual space, geographical boundlessness, and anonymity provide a significant advantage for minority groups (or disadvantaged groups) in the international era to pursue social support [43].…”
Section: Participating In Online Communities For Social Support Durin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurs arguably function as unsung heroes during a pandemic-induced economic crisis of the current magnitude (Maritz et al, 2020). They are expected not only to sustain their firms but also to identify and develop any new opportunities that could prove beneficial (Lim et al, 2020; Morgan et al, 2020; Meurer et al, 2021; Zhang et al, 2021). Yet, only a few studies have examined the linkage between crisis and entrepreneurship in general (Devece et al, 2016; Doern, 2016; Doern et al, 2019).…”
Section: Introductionmentioning
confidence: 99%